2016
DOI: 10.1111/crj.12556
|View full text |Cite
|
Sign up to set email alerts
|

EBUS may arise as an initial time saving procedure in patients who are suspected to have small cell lung cancer

Abstract: EBUS-TBNA may be an initial diagnostic procedure in SCLC. Patients with only hilar/mediastinal masses without any endobronchial lesion could be directed to centers with the capability for performing EBUS-TBNA to have a rapid diagnosis without any time loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…Only 16.6% (28/169) of patients required more than one procedure compared to 28.4% (215/756) of patients who did not initially undergo EBUS. Other studies have shown similar results . These studies also showed a positive correlation between the time to diagnosis and treatment decisions and survival .…”
Section: Discussionsupporting
confidence: 74%
“…Only 16.6% (28/169) of patients required more than one procedure compared to 28.4% (215/756) of patients who did not initially undergo EBUS. Other studies have shown similar results . These studies also showed a positive correlation between the time to diagnosis and treatment decisions and survival .…”
Section: Discussionsupporting
confidence: 74%
“…They found that both time intervals were significantly shorter in patients in which the first diagnostic procedure was EBUS‐TBNA, compared with patients in which other procedures were undertaken first. The authors noted that, for patients with extensive disease, the diagnostic work‐up time nearly equalled their expected survival time, if they did not receive treatment …”
Section: Resultsmentioning
confidence: 99%
“…The effects of this multifunctionality are evident from the results of the Lung‐BOOST trial, where EBUS‐TBNA was able to reduce the mean time to treatment decision by half, mainly by reducing the number of outpatient appointments and investigations . It has been suggested that, if the presenting hospital does not have the capability to perform EBUS‐TBNA, then patients that are candidates for EBUS‐TBNA (probable or proven mediastinal involvement, absence of metastatic disease) should be referred to centres that do . Importantly, if after the initial CT there is evidence of a peripheral lung lesion and mediastinal involvement, and EBUS‐TBNA is not available, then the next step should not be a CT‐guided biopsy of the peripheral lesion, as it will only provide diagnostic but not staging information.…”
Section: Resultsmentioning
confidence: 99%
“…Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) is a minimally invasive modality for nodal staging in lung cancer patients . In addition, EBUS‐TBNA is widely used for the diagnosis of benign conditions, for example, sarcoidosis related mediastinal and hilar lymphadenopathy …”
Section: Introductionmentioning
confidence: 99%
“…Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive modality for nodal staging in lung cancer patients. [1][2][3][4][5] In addition, EBUS-TBNA is widely used for the diagnosis of benign conditions, for example, sarcoidosis related mediastinal and hilar lymphadenopathy. 6,7 The observation that certain histologic subtypes of nonsmall cell lung cancer (NSLC) respond differently to particular chemotherapeutic agents and the increasing use of targeted therapies, 8,9 have created a need for precise histologic characterization and molecular analysis for targeted mutations of small biopsy specimens obtained by EBUS-TBNA.…”
Section: Introductionmentioning
confidence: 99%